Significant Efficacy of Tramadol/Acetaminophen in Elderly Patients with Chronic Low Back Pain Uncontrolled by NSAIDs: An Observational Study - Imamura, Toshihiro (Open Orthop J, 2015)
Chronic low back pain (LBP) is a common condition and is generally treated using non-steroidal anti-inflammatory drug (NSAID); however, chronic NSAID use can decrease renal function. Tramadol, a weak opioid agonist, may improve chronic LBP and disability, while avoiding adverse effects such as gastrointestinal and renal toxicity. However, few studies have evaluated the short-term efficacy of opioids in Asian patients with chronic LBP. In this study, 24 patients with chronic LBP unresponsive to NSAIDs (10 men, 14 women; mean age, 65.1 ± 12.1 years) were prescribed tramadol/acetaminophen (37.5 mg/325 mg; four tablets daily) for 1 month. Then, the following parameters were assessed at baseline and after 1 week and 1 month of treatment: leg pain and LBP (Visual Analog Score [VAS]); activity of daily life (Roland-Morris Disability Questionnaire [RDQ]); and disability (Oswestry Disability Index [ODI]). Leg pain resolved within 1 week (p = 0.00093); however, LBP was relieved only at 1 month (p = 0.00034). The mean RDQ (p = 0.015) and ODI (p = 0.0032) scores were improved at 1 month. A total 41.6% of patients reported nausea and floating sensation beginning tramadol/acetaminophen treatment, and 12.5% (four patients) discontinued treatment as a result. LBP did not improve in 25% of patients administered tramadol/acetaminophen. Because this was an observational study, rather than a comparative study, further investigation is needed to evaluate the long-term efficacy of tramadol/acetaminophen in elderly patients with chronic LBP unresponsive to NSAIDs.